2019
DOI: 10.1111/acv.12488
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in the response of tiger gene flow to landscape features and limiting factors

Abstract: Integrated landscape management of key population areas along with the corridors linking them is important for tiger conservation in the Indian subcontinent. Relationships between gene flow and landscape patterns, however, cannot be generalized given that different limiting factors influence movement in different spatial contexts. Here, we study the landscape features affecting tiger gene flow in the Western Ghats, and examine how and why limiting landscape features differ between Central India and the Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…However, many areas that are potentially of the highest inherent ecological stability for wildlife are also facing the greatest impact by humans. These rough landscapes likely offer refugia from human disturbance for large mobile species such as tigers (Krishnamurthy et al 2016;Reddy et al 2019) as well as smaller meso-carnivores like yellow-throated marten (Vergara et al 2016). Approximately 50% of the modelled species were negatively associated with agriculture, suggesting that a landscape perforated or fragmented by agriculture, in general, is less suitable for the occurrence of the wildlife species (Table 2).…”
mentioning
confidence: 99%
“…However, many areas that are potentially of the highest inherent ecological stability for wildlife are also facing the greatest impact by humans. These rough landscapes likely offer refugia from human disturbance for large mobile species such as tigers (Krishnamurthy et al 2016;Reddy et al 2019) as well as smaller meso-carnivores like yellow-throated marten (Vergara et al 2016). Approximately 50% of the modelled species were negatively associated with agriculture, suggesting that a landscape perforated or fragmented by agriculture, in general, is less suitable for the occurrence of the wildlife species (Table 2).…”
mentioning
confidence: 99%
“…We studied 599 tigers across the tiger range at the Taqpep c.1360C > T variant site. We genotyped 85 tigers using whole-genome data for four subspecies [Amur, Malayan, and Sumatran: 29 (44), and ongoing studies in Central India, North, and northeast India]. Of these, 309 individuals (58.5%) were successfully genotyped and were homozygous for the wild-type allele.…”
Section: Resultsmentioning
confidence: 99%
“…We genotyped 85 tigers using whole-genome data for four subspecies [Amur, Malayan, and Sumatran: 29, Armstrong et al ( 40 ), and Bengal tigers: 56, Khan et al ( 5 ), Khan et al ( 41 ), Armstrong et al ( 40 ), and this study] and recorded all of them as homozygous for the wild-type allele. We also attempted to PCR amplify the Taqpep c.1360C > T mutation locus ( Methods ) from 528 genetically identified individuals from primarily noninvasive sources [samples from Natesh ( 42 ), Reddy et al ( 43 ), Reddy et al ( 44 ), and ongoing studies in Central India, North, and northeast India]. Of these, 309 individuals (58.5%) were successfully genotyped and were homozygous for the wild-type allele.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results highlight the importance for landscape models to be developed specific to the region of interest as a precursor to conservation management decisions, and for the effects of spatial nonstationarity to be carefully considered and evaluated in any application of connectivity modelling. In a study through both central and western India, Reddy et al (2019) found tiger movements to be primarily related to topographic roughness and secondarily to diffuse disturbance. However, the relationship between the tiger and these two limiting factors was inverted between the west and central India, suggesting that a resistance surface built from a spatially constant functional relationship would at best be appropriate for only one of these two regions.…”
Section: Spatial Variabilitymentioning
confidence: 99%